Faktor Dominan pada Indeks Inklusi Perbankan Syariah Sektor Pertanian di Indonesia - Eko Fajar Cahyono; M. Faris Fadillah Mardianto; Sylva Alif Rusmita (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2017)
The importance of financial inclusion in Islamic Bank is not only affordable for business level, but also agricultural sector. Indonesian Islamic banking as one of the providers of financial services continued to grow, but its market share is still small compared with conventional banking. Therefore financial inclusion Islamic banking, especially in reaching out to the agriculture sector, need to be improved. This study aims to measure the value of financial inclusion Islamic banks in Indonesia province in reaching the agricultural sector, both provincial and district or city. Indexing method factor analysis (Principal Component Analysis) using 14 indicators that have been adapted to the concept of Financial Inclusion Index (FII). Data correlated with Islamic Financial Institution availability can be divided into two factors which are of Islamic banking (including Islamic windows of the conventional bank) and Islamic Rural Bank. The result of the analysis is indicating that the most dominant factor provided by Islamic banking (including Islamic windows of conventional Bank). The result also present the highest index score reached by West Java Province and East Java, while the lowest index score reached by East Nusa Tenggara and West Papua Province.Keuangan inklusi bagi bank syariah sangatlah penting, bukan hanya memberikan pembiayaan pada sektor bisnis namun juga untuk sektor pertanian. Bank syariah di Indonesia sebagai salah satu lembaga keuangan yang terus berkembang memiliki potensi untuk mengembangkan keuangan inklusi walaupun pangsa pasar dari bank syariah masih lebih kecil dibandingkan konvensional. Keberadaan keuangan inklusi di bank syariah khususnya pada sektor pertanian masih perlu ditingkatkan Penelitian ini bertujuan untuk mengukur nilai keuangan inklusi di bank syariah pada sektor pertanian di seluruh provinsi yang ada di Indonesia, baik pada level provinsi, kabupaten dan kota. Penelitian ini menggunakan metode index faktor analisis (analisis komponen prinsip) dengan 14 indikator yang diadaptasi dari konsep Indeks Inklusi Keuangan. Data-data berkenaan dengan lembaga keuangan Islam yang tersedia dapat dibagi menjadi dua factor, yaitu faktor yang berkaitan dengan bank syariah (termasuk unit usaha syariah) dan Bank Pembiayaan Rakyat Syariah. Hasil analisis menunjukkan bahwa faktor yang paling dominan adalah faktor yang berkaitan dengan bank syariah dan unit usaha syariah. Hasil menunjukkan bahwa angka indeks tertinggi diraih oleh provinsi Jawa Barat dan Jawa Timur, sedangkan angka indeks terendah diraih oleh provinsi Nusa Tenggara Timur dan Papua Barat.